The Effect of Consuming Sago (Metroxylon sagu Rottb) Once a Day on Changes in Blood Glucose Levels of Diabetes Mellitus Sufferers in the Matandahi and Motui Community Health Centers - Irawati Ali Djatmo; La Ode Saafi; Sri Anggarini (Waluya The International Science of Health Journal, 2026)
Introduction: Diabetes Mellitus (DM) is a chronic disease that can lead to various complications such as premature death, blindness, heart disease, and kidney failure. The prevalence of DM at Matandahi Community Health Center in 2022 was 5.9% and increased to 6.8% in 2023. Meanwhile, at Motui Community Health Center, it was 7.1% in 2022 and 8.7% in 2023. The purpose of this study was to determine the effect of consuming sago (Metroxylon sagu Rottb) once a day on changes in blood glucose levels of Diabetes Mellitus sufferers in the Matandahi and Motui Community Health Center work area. Method: This type of research is quantitative (pre-experimental), with one group pre-test-post-test design. The sample is 30 type 2 DM patients registered at the Matandahi and Motui Community Health Centers, taken using a simple random sampling technique. Random blood glucose levels were obtained using a portable Easy Touch Meter. Data were analyzed using a paired t-test, one-way ANOVA, and continued with the Least Significant Difference (LSD) test. Result: The results of the study showed that the average blood glucose level, before consuming sago once a day in the paired t-test, obtained a p value of 0.001 (sago consumption once a day).  Conclusion: There is an effect of consuming sago once, so it is recommended that Matandari Health Center implement socialization of the importance of consuming sago for Diabetes Mellitus sufferers.